Global value chain governance: A relational perspective - Kano, Liena (Journal of International Business Studies, 2018)
Global value chain (GVC) governance is an established field within international business research, yet the relational aspects of GVCs have, to date, garnered less scholarly attention than have efficiency considerations. This conceptual study’s objective is to explore the relational dynamics of GVC governance using an internalization theory perspective, and by linking GVC research with insights from the business network literature. GVCs are argued to be a distinct form of asymmetrical networks, associated with economizing and capability creation features, as well as costs. The orchestrating firm can thus enhance efficiency outcomes of the GVC using social mechanisms similar to those adopted by core actors in a business network. In the study, six such mechanisms were identified: (1) selectivity, (2) inclusion of non-business intermediaries, (3) joint strategizing, (4) relational capital, (5) multilateral feedback, and (6) rules for equitable value distribution. While safeguarding the GVC’s efficiency, the above social mechanisms are associated with challenges and limitations, and therefore do not guarantee international competitive success. However, deployed in an integrative fashion, these social mechanisms facilitate coordination (thus economizing on bounded rationality), reduce the hazards of imperfect effort by partners (thus economizing on bounded reliability), and foster innovation and new capability development.